The instructive power of the fable in New Zealand's Native School Reader (1886). Issue 1 (5th June 2017) - Rogers, Shef
Abstract : Purpose: The purpose of this paper is to examine the cultural implications of James Henry Pope's selection of fables for his 1886 Native School Reader designed to teach English to Māori students in Native Schools. Design/methodology/approach: The essay takes a historical approach. It surveys attitudes towards the fable as a pedagogical tool prior to 1880 and reviews Pope's choice of 50 from the 300 available fables in the Aesopic canon. Findings: The study finds that Pope was well informed and well intentioned, but nonetheless appeared to be unaware of potentially unsettling interpretations of his selected fables. Originality/value: While it may be relatively easy for twenty-first-century readers to perceive the cultural tensions of Pope's work, exploring the historical context helps us to understand both why Pope compiled the text he did, and why he and his books were well regarded by both Pākehā and Māori, despite almost certainly not conveying the values the settlers wished to inculcate in Māori.